PEMBERDAYAAN DAN KEMANDIRIAN BAGI KESEHATAN LANJUT USIA MELALUI SEKOLAH ADIYUSWO : EMPOWERMENT AND INDEPENDENCE FOR ELDERLY HEALTH THROUGH ADIYUSWO SCHOOL - Harsoyo; Setyohadi Pratomo (Jurnal Suara Pengabdian 45, 2022)
The protection, welfare and independence of the elderly group is increasingly important in line with the increasing number of elderly people, welfare and the realization of an elderly friendly city in Surakarta. The Adiyuswo (Olderly) School in implementation in the City of Surakarta is closely related to the policy steps to realize an elderly-friendly city and the inclusive city policy that has been established by the City of Surakarta since 2006. The policy direction is contained in the Surakarta City Medium-Term Development Plan 2021-2026 with The leading implementing sectors are the Social Service (Dinas Sosial) and Bappeda as the coordinator of regional development planning. The implementation of policies regarding Adiyuswo Schools (Seniors) is carried out in accordance with the direction of the policy on Lifelong Education through regular and planned non-formal education. This education is carried out in an equal and participatory manner. In this case, facilitators, mentors and health and social services are prepared through local institutions, either through the Elderly Committee, Elderly Forums in sub-districts and institutions in the village through fostering elderly families. The elderly school involves the target group, namely the pre-elderly population, the elderly group and other family members who take care of the elderly in the household.